Well‐Defined Pillararene‐Based Azobenzene Liquid Crystalline Photoresponsive Materials and Their Thin Films with Photomodulated Surfaces. (7th May 2015) - Pan, Shi; Ni, Mengfei; Mu, Bin; Li, Qian; Hu, Xiao‐Yu; Lin, Chen; Chen, Dongzhong; Wang, Leyong
<x xml:space="preserve">Abstract</x> Photoresponsive materials (PRMs) have long been a hot topic and photo‐modulated smart surface is very appealing. Particularly, liquid crystalline PRMs are able to amplify and stabilize photoinduced orientation thanks to their self‐assembling and ordering characteristics. Herein, the first pillararene‐based azobenzene liquid crystalline PRM with well‐defined structure is presented, which can avoid the usually ill‐defined composition drawback of polymer PRMs and prevent the severe H‐aggregation from suppressing or even completely blocking photoresponse in simple azobenzene derivatives. The pillar[5]arene‐based macrocyclic azobenzenes with variant length spacers show wide temperature range smectic liquid crystalline mesophases and excellent film‐formation property. The tubular pillar[5]arene macrocyclic framework provides sufficient free volume for azobenzene moieties to achieve reversible photoisomerization and photoalignment; thus, their thin films demonstrate excellent light‐triggered modulation of surface free energy, wettability, and even photoalignment‐mediated orientation of an upper layer discotic liquid crystal columnar mesophase. Such pillararene‐based azobenzene liquid crystals represent novel and promising PRMs with extensive fascinating applications.